A study of alienation and personality traits conducted among "Coloured" and white males in South Africa - Shaw, Patrick Donovan Richard (Rhodes University, Faculty of Humanities, Department of Psychology, 1987)
A measure of four types and five contexts of alienation, as well as ten personality traits, was obtained via the Â·application of the Alienation Test and Howarth's Personality Questionnaire. The sample (~= 195) comprised of both high school pupils and adults drawn from the local population of English and Afrikaans speaking Whites and "Coloureds" from a town in the Eastern Cape of South Africa. These six sample groups allowed for comparisons on the measures for factors such as race, age and cultural differences. The literature review showed repeated reference to the "alienation" of the "Coloured" people of South Africa in the political, social and cultural spheres. However, the research in this area has been sparse. The main object of the study, therefore, was to determine if "Coloureds" do feel alienated, as well as the contexts of this alienation, using Whites as a comparative group. possible differences in personality traits between "Coloureds" and Whites have been associated with the differences in behaviour exhibited by these two groups, but past research has failed to find many differences. The second objective of this study, therefore, was to determine if there are differences between the personality traits of "Coloureds" and Whites, and to extend the past research. Researchers have shown that there is a relationship between alienation and personality traits, but have not adequately addressed the nature of this relationship or its implications. Following from this, the third objective of the study was to examine the relationship between alienation and personality traits, as well as their ability to predict alienation. Results on the Alienation Test showed that "Coloureds" do differ significantly from Whites and exhibit far higher levels of alienation. These differences are most marked on those types and contexts of alienation reflecting a distance from the social and political environment. Results on the personality measure showed minimal differences in personality traits between the groups. Where they were evident, they could be attributed to environmental factors. Lastly, there was a relationship between alienation and certain personality traits, but these traits had limited power to predict alienation. Taking all findings of the study into account, it is evident that the social environment, and specifically a discriminatory social environment, affects feelings of alienation to a far greater extent than personality traits. In addition, the large differences in scores of the "Coloured" and White groups on the measure of alienation and the minimal differences on the measure of personality, provides evidence that what is measured by alienation and what is measured by personality traits, are two distinctly different constructs.
Keywords: Alienation (Social psychology); Alienation (Social psychology) -- Case studies -- South Africa